Efisiensi dan Fouling Factor Sealtube Heat Exchanger Pada Proses Pendinginan Refined Bleached Deodorized Palm Oil - Panjaitan, Jabosar Ronggur Hamonangan; Nurhasanah, Nurhasanah; Atikasari, Laela Febby; Ponilawati, Ponilawati (Rekayasa, 2022)
Refined Bleached Deodorized Palm Oil (RBDPO) is a product of the crude palm oil (CPO) refining process. RBDPO is one of Indonesia's strategic commodities for low price cooking oil production. The cooking oil processing uses a heat transfer device such as heat exchanger. Heat exchanger sealtube 881X is a tool that used in the heat recovery unit at PT. Tunas Baru Lampung, Tbk refinery plant. Heat exchanger sealtube 881X used to cool refined bleached deodorized palm oil (RBDPO) to 95 – 105oC from the deodorization process by utilizing cooling water. In this research, the efficiency and fouling factor of the heat exchanger sealtube 881X were calculated at PT. Tunas Baru Lampung, Tbk refinery plant. Based on the results, it can be seen that the actual efficiency of Heat exchanger sealtube 881X was between 71-87%. Changes in the value of fouling factor affect the thermal efficiency of the heat exchanger sealtube 881X which from the calculation results, the highest fouling factor value was 0.0017.